Pengaruh Penyuluhan terhadap Pengetahuan Kader tentang Open Defecation Free di Kota Cirebon: The Influence of Counseling on Cadres' Knowledge about Open Defecation Free in Cirebon City - Jaenudin, Jaenudin; Andhini, Citra Seto Dwi; Nurhaeni, Ani; Andini, Dea; Saharani, Widya (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
One of the targets of the Sustainable Development Goals is ending Open Defecation globally in 2030. Data from the Cirebon City Health Office shows that Lemahwungkuk Village, which is in the working area of the Cangkol Community Health Center, is the only area in Cirebon City that is not yet free from Open Defecation Free (ODF). As the front guard in health services in the community, health cadres need to be educated about ODF to increase their knowledge so that it can be disseminated to the community in an effort to stop ODF. The research design is a quasi-experiment with a pre-test and a post-test. The population is cadres at the Cangkol Community Health Center, Cirebon City, with a sample size of 34 respondents, using accidental sampling. Data was obtained primarily through the use of a questionnaire. Data were analyzed univariately and bivariately with statistical tests, such as the paired t-test. Before the extension, there were 24 cadres whose knowledge was in the good category (70.6%). Meanwhile, 32 people (94.1%) were mostly good after counseling. Statistical test results (p-value=0.000) with a difference of 1.06. There is a significant influence of extension activities on cadres' knowledge about Open Defecation Free in Cirebon City.